The Application of Digital Technologies in Arabic Language Learning: An Analytical Review of the Literature - Nafisah, Ainun; Dinina, Emil Naila Sa'da; Rifqi, Mohammad Aziz; Arofah, Siti (IJIE International Journal of Islamic Education, 2025)
Technology in education refers to the use of various digital tools and innovative approaches to enhance the effectiveness and quality of learning. In Arabic language learning, technology has undergone significant development, beginning with audio-visual media and evolving into e-learning platforms, mobile applications, artificial intelligence, and internet-based interactive learning environments. This progression reflects the increasing need for more flexible, engaging, and learner-centered instructional practices. This study aims to examine the roles, utilization, challenges, and technological innovations in Arabic language learning through a library research method. The focus of the study is the analysis of scholarly articles published in academic journals that discuss the integration of technology in the Arabic language learning process. Data are collected from various credible sources, including scientific journals, academic books, and relevant scholarly documents. The findings indicate that technology plays an essential role in improving Arabic language learning by making it more engaging, effective, and responsive to learners’ needs. Digital learning media such as educational applications, e-learning platforms, and interactive tools contribute to increased student motivation and learning interest. Moreover, recent technological innovations—including AI, virtual reality, augmented reality, podcasts, and interactive videos—have enriched teaching strategies and expanded learning opportunities. Applications such as Duolingo, Mondly, Google Classroom, and Quizizz support flexible, accessible, and enjoyable learning experiences. Overall, the integration of technology provides positive contributions not only to the learning process but also to the assessment and evaluation of Arabic language learning outcomes.